Contribution to the study of experimental altitude sickness - Pulmonary Manifestations of cuy in acute mountain sickness - Mori Chávez, P. (1935)
In the study of this interesting disease entity called the "altitude sickness", has already passed the stage of observation and physiological and clinical description, which was as accurately traced by Professor Monge and colleagues in the two forms of this evil: The acute, hitherto the only known, or the "evil mountain" or "mountain sickness" itself, which is nothing but an imbalance, maladjustment or failure of compensatory mechanisms of the body determined by an abrupt change from natural conditions of life on the plains, going to a rarefied atmosphere of height. Chronic, slowly, mismatch, leading to disorders, more or less severe, or the "erythremia Heights" or "disease of the Andes", and known as the "disease Monge".